A Synthetic DNA Construct to Evaluate the Recovery Efficiency of Cell-Free DNA Extraction and Bisulfite Modification. (21st June 2021) - Goh, Su Kah; Cox, Daniel R A; Wong, Boris Ka Leong; Musafer, Ashan; Witkowski, Tom; Do, Hongdo; Muralidharan, Vijayaragavan; Dobrovic, Alexander
Abstract: Background: Despite improvements in the genetic and epigenetic analysis of cell-free DNA (cfDNA), there has been limited focus on assessing the preanalytical variables of recovery efficiency following cfDNA extraction and bisulfite modification. Quantification of recovery efficiency after these steps can facilitate quality assurance and improve reliability when comparing serial samples. Methods: We developed an exogenous DNA Construct to Evaluate the Recovery Efficiency of cfDNA extraction and BISulfite modification (CEREBIS) after cfDNA extraction and/or subsequent bisulfite modification from plasma. The strategic placement of cytosine bases in the 180 bp CEREBIS enabled PCR amplification of the construct by a single primer set both after plasma DNA extraction and following subsequent bisulfite modification. Results: Plasma samples derived from 8 organ transplant donors and 6 serial plasma samples derived from a liver transplant recipient were spiked with a known number of copies of CEREBIS. Recovery of CEREBIS after cfDNA extraction and bisulfite modification was quantified with high analytical accuracy by droplet digital PCR. The use of CEREBIS and quantification of its recovery was useful in identifying problematic extractions. Furthermore, its use was shown to be invaluable towards improving the reliability of the analysis of serial samples. Conclusions: CEREBIS can be used as a spike-in control to address the preanalytical variable of recovery efficiency both after cfDNA extraction from plasma and following bisulfite modification. Our approach can be readily implemented and its application may have significant benefits, especially in settings where longitudinal quantification of cfDNA for disease monitoring is necessary.